THE GROWTH AND THE YIELD OF Asystasia gangetica (L.) subsp. Micrantha FERTILIZED WITH SLAUGHTER HOUSE WASTE PLUS LIME AND SAWDUST - A. P., Kwarta; Roni, N. G. K.; Suryani, N.N (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
This study was conducted to determine the growth and the yield of Asystasia gangetica (L.) subsp. Micrantha fertilized with slaughter house waste plus lime and sawdust. The research was carried out in the greenhouse, Sesetan Research Station, Animal Husbandry Faculty, Udayana University on Markisa Alley of Sesetan Street for 8 (eight) weeks. This study used a completely randomized design (CRD) method with 4 (four) treatments and 7 (seven) replications so that there were 28 experimental units. The treatment given was a dose of abattoir waste fertilizer added with lime and sawdust consisting of 0 ton ha -1 , 10 tons ha -1 , 20 tons ha - 1, and 30 tons ha -1 . The variables observed were growth variables, yield variables, and growth characteristics. The results showed that the slaughter house waste fertilizer added with lime and sawdust had not been able to increase the growth variables, yield variables, and growth characteristics variables. Dosage of 20 tons ha -1 produced an average plant height of 33.81 cm, the number of leaves was 69.29 and the number of branch was 20. The dosage tended to be the highest compared to doses of 0 ton ha -1 , 10 tons ha -1 , and 30 tons ha -1 . The treatment dose of 20 tons ha -1 on the total dry weight of forage showed the highest average of 2.21 g, and the treatment dose of 10 tons ha -1 on the ratio of the total dry weight of forage to dry weight of roots showed the highest average of 0.88 g. It was concluded that the application of slaughter house waste fertilizer plus lime and sawdust had not been able to increase the growth and yield of Asystasia gangetica (L.) subsp. Micrantha plants. Keywords: Asystasia gangetica (L.) subsp. Micrantha , growth, organic fertilizer, yield